An analysis of the performance of central and barrio school pupils in the province of Iloilo in a mathematics proficiency test - Alcarde, Maria Lita Cataluña 1950- (1973)
The aim of the study is to find answers to some of the many problems regarding mathematics teaching in the public elementary schools in the province of Iloilo for the school year 1972-1973. It is an attempt to determine the proficiency levels of elementary pupils in grade six in the province and to compare the performance of the central and the barrio school pupils.